TNFAIP3 Gene Polymorphisms in Three Common Autoimmune Diseases: Systemic Lupus Erythematosus, Rheumatoid Arthritis, and Primary Sjogren Syndrome—Association with Disease Susceptibility and Clinical Phenotypes in Italian Patients. (27th August 2019) - Ciccacci, C.; Latini, A.; Perricone, C.; Conigliaro, P.; Colafrancesco, S.; Ceccarelli, F.; Priori, R.; Conti, F.; Perricone, R.; Novelli, G.; Borgiani, P.
Abstract : Autoimmune diseases (AIDs) are complex diseases characterized by persistent or recurrent inflammation, alteration of immune response, and production of specific autoantibodies. It is known that different AIDs share several susceptibility genetic loci. Tumor necrosis factor alpha inducible protein 3 (TNFAIP3) encodes the ubiquitin-modifying enzyme A20, which downregulates inflammation by restricting NF- κ B, a transcription factor that regulates expression of various proinflammatory genes. Variants in TNFAIP3 gene have been described as associated with susceptibility to several AIDs. Here, we analyzed two TNFAIP3 polymorphisms in Italian patients with systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and primary Sjogren's syndrome (pSS), to verify if the genetic variability of TNFAIP3 gene is involved in genetic predisposition to AIDs also in the Italian population. We recruited 313 SLE patients, 256 RA patients, 195 pSS patients, and 236 healthy controls. Genotyping of rs2230926 and rs6920220 in TNFAIP3 gene was performed by an allelic discrimination assay. We carried out a case/control association study and a genotype/phenotype correlation analysis. A higher risk to develop SLE was observed for rs2230926 (P = 0.02, OR = 1.92 ). No association was observed between this SNP and the susceptibility to pSS or RA. However, the rs2230926 variant allele seems to confer a higher risk to develop lymphoma in pSS patients, while in RA patients, the presence of RF resulted significantly associated with the variant allele. Regarding the rs6920220 SNP, we observed a significant association of the variant allele with SLE (P = 0.03, OR = 1.53 ), pSS (P = 0.016, OR = 1.69 ), and RA (P = 0.0001, OR = 2.35 ) susceptibility. Furthermore, SLE patients carrying the variant allele showed a higher risk to develop pericarditis, pleurisy, and kidney complications. Our results support the importance of the TNFAIP3 gene variant role in the development of different autoimmune diseases in the Italian population and furtherly confirm a sharing of genetic predisposing factors among these three pathologies.